Konsekuensi Hak Tanggungan Perjanjian Kredit Antara Kreditor dan Debitor - Martinus Al Ibrani Giga Taufano; Wilma Silalahi (UNES Law Review, 2024)
An agreement is the basis for the implementation of activities that bind the parties with an orientation towards the goals to be achieved. In the agreement, the parties agree to comply with the contents of the agreement, which gives birth to a legal relationship, this can be reformulated as, "Therefore, if one party fails to fulfill its responsibilities, the other party has the right to demand the performance of these obligations. In Indonesia, credit agreements are expressly regulated in Law no. 10/1998, which describes a loan facility as a loan that must be repaid after a certain period of time with interest. The creditor, who facilitates the loan, and the debtor, who borrows, are bound parties. Credit agreements generally have collateral, such as security rights, which are closely related to the repayment of the debt. Nonetheless, cases of default still occur frequently, indicating the need for clearer legal protection for both parties. This research uses a normative legal approach and descriptive analysis to understand the consequences of disputes in credit agreements and the role of mortgage rights in them.